VD_FINDINFO ML / 2013 / 349 vom 17. Dezember 2013 - VD Tribunal cantonal (2013)
COMMANDEMENT DE PAYER, CRÉANCE, MENTION, CAUSE DE L'OBLIGATION, TITRE DE MAINLEVÉE | 3 al. 2 CC, 67 al. 1 ch. 4 LP, 69 al. 2 ch. 1 LP, 80 al. 1 LP